Sunsetpreneur : Menggali Potensi UMKM di Sunbae Kawasan Manado Melalui Konsep Nongkrong Outdoor yang Unik - Rexy Andalangi Maatuil,; Muarif, Jeysicha; Aprilia Belinda Kandijoh, (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study explores the integration of outdoor leisure spaces as a strategy to strengthen local MSMEs in the Sunbae area of ​​Manado. Findings indicate that MSMEs effectively leverage local potential, including materials, cultural values, and the coastal atmosphere, to create distinctive products and experiences. Collaboration between MSME owners, the creative community, and local artists significantly increases visitor engagement and strengthens social networks. The concept of an outdoor leisure space also functions as a third place, where design elements such as lighting, comfortable seating, and a breezy beach atmosphere encourage visitors to stay longer and contribute to higher economic activity. Digital technology, particularly social media marketing and QRIS-based transactions, further enhances the competitiveness of MSMEs. The study also identifies challenges related to weather, visitor fluctuations, and dependence on events. Overall, Sunbae demonstrates that combining creative public spaces, community interaction, and technology can create a sustainable local economic ecosystem and increase the resilience and visibility of MSMEs.